Integrating Modern Sundanese Architecture in Mountain Villa Design and Planning for Tourism - Ahmad Ghazy Dananjaya (Advances in Civil Engineering and Sustainable Architecture, 2025)
This study examines the integration of modern Sundanese architecture in mountain villa design and planning in Pagerwangi, Lembang, to support sustainable tourism. Using an inferential quantitative approach, data from structured surveys and observations reveal significant correlations between traditional materials, craftsmanship, and cultural symbolism with tourist preferences. The findings highlight the appeal of culturally authentic designs that combine vernacular elements with contemporary styles. Challenges in modern villa construction, such as neglecting cultural values, are addressed with recommendations for incorporating cultural heritage into design principles. This participatory approach emphasizes involving local communities to ensure sustainability and authenticity. Practical insights are offered for developers and policymakers to enhance tourism planning by creating culturally resonant and sustainable tourist destinations. The study underscores the value of modernizing traditional architecture to meet contemporary demands while preserving cultural identity.